08B1‐1: an automated beamline for macromolecular crystallography experiments at the Canadian Light Source. (1st May 2014) - Fodje, Michel; Grochulski, Pawel; Janzen, Kathryn; Labiuk, Shaunivan; Gorin, James; Berg, Russ
<x xml:space="preserve">Abstract</x> Beamline 08B1‐1 is a recently commissioned bending‐magnet beamline at the Canadian Light Source. The beamline is designed for automation and remote access. Together with the undulator‐based beamline 08ID‐1, they constitute the Canadian Macromolecular Crystallography Facility. This paper describes the design, specifications, hardware and software of beamline 08B1‐1. A few scientific results using data obtained at the beamline will be highlighted.